A whole system approach to childhood obesity: How a supportive environment was created in the city of Brighton and Hove, United Kingdom - Salm, Leah; Nisbett, Nicholas; Cuming, Katie; Hrynick, Tabitha; Lulache, Alexandra; MacGregor, Hayley (Springer, 2023)
Childhood obesity is a growing global challenge, and no country has yet reversed the upward trend in prevalence. The causes are multifaceted, spanning individual, societal, environmental, and political spheres. This makes finding solutions complex as traditional linear models of treatment and effect have proven only minimally successful or unfeasible at the population level. There is also a paucity of evidence of what works, and few examples of intervention that operate on a ‘whole systems’ level. The city of Brighton in the United Kingdom has experienced a downward trend in child obesity rates compared to national figures. The aim of this study was to explore what has led to successful change in the city. This was done through a review of local data, policy and programs, and thirteen key informant interviews with key stakeholders involved in the local food and healthy weight agenda. Our findings highlight key mechanisms that have plausibly contributed to a supportive environment for obesity reduction in Brighton according to key local policy and civil society actors. These mechanisms include; a commitment to early years intervention such as breastfeeding promotion; a supportive local political context; the ability to tailor interventions to community needs; governance structures and capacity that enable cross-sectoral collaboration; and a citywide framing of obesity solutions in the context of a ‘whole system’ approach. However, substantial inequalities persist in the city. Engaging families in areas of high deprivation and operating in an increasingly difficult context of national austerity are persistent challenges. This case study sheds light on some mechanisms of what a whole systems approach to obesity looks like in practice in a local context. This is of relevance to both policymakers and healthy weight practitioners across a spectrum of sectors who need to be engaged to tackle child obesity.